1997
DOI: 10.2307/2657359
|View full text |Cite
|
Sign up to set email alerts
|

Political Generations, Micro-Cohorts, and the Transformation of Social Movements

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to American Sociological Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(179 citation statements)
references
References 33 publications
3
167
0
9
Order By: Relevance
“…But the composition of a movement may change -for instance from self-help groups around battered women to radical feminist-ideology groups -and, as a consequence, people may feel less akin to the others in the movement (Whittier, 1997). Schisms are another reason why movements fail to satisfy identity motives.…”
Section: The Dynamics Of Disengagementmentioning
confidence: 99%
“…But the composition of a movement may change -for instance from self-help groups around battered women to radical feminist-ideology groups -and, as a consequence, people may feel less akin to the others in the movement (Whittier, 1997). Schisms are another reason why movements fail to satisfy identity motives.…”
Section: The Dynamics Of Disengagementmentioning
confidence: 99%
“…New blood is not only important to keep up the movements' numbers. Whittier (1997) found that, among others things, the external context of the movement at the time of entry of new participants defines a 'generation' of activists. These generations then subsequently contribute 'to produce change in social movements' and 'alter the movement's direction' (Whittier 1997, p. 761).…”
mentioning
confidence: 99%
“…Give the shortage of space, two observations need to be made in order to assist the reader. The operational definition of social movements with which we shall work here is composed out of elements seen to recur in the concepts of the main authors on the subject (Tarrow 1998;Tilly1999;Amenta 2006;Guigni 1999 andWhittier 1997) 4 . That definition is: a social movement is a series of collective contentious performances extending over time through which groups and networks of people under a shared frame challenge the authorities and stake claims in the name of a broader public.…”
Section: Social Movements and The Institutionalization In The Proposimentioning
confidence: 99%